Essays in Industrial Organization - Li, Ying (2015)
This dissertation consists of three chapters investigating the effect of firms' entry and exit behavior on market outcomes. Chapters 1 and 2 relate to the recent financial crisis in the auto industry that led to General Motor and Chrysler's bankruptcy filing and their dealer network reconstruction, studying firms and consumers' response to this industry shock. Chapter 3 challenges the current merger policy by proposing a selective entry mechanism. The first chapter examines the impact of new car dealer closures on surviving dealers' profitability and consumer welfare during General Motor and Chrysler's bankruptcy restructuring. Using a complete sample of new car transaction data from 2007 to 2013 in Iowa, I estimate the effect of changes in dealer networks on surviving dealers' sales, prices, and consumer welfare by building a structural model with spatial differentiation and conducting counterfactual analysis. I further estimate this effect by conducting retrospective analysis. These two methods are compared, and the results validate the assumptions of the structural model. The second chapter empirically investigates the effect of financial distress on used car prices and sales. When purchasing durable goods such as cars, consumers are expected to respond to the likelihood of default for auto makers because it will affect the provision of warranty and future maintenance service, as well as availability of parts. I find that a 10% increase in the likelihood of bankruptcy results in a $86 price drop in used cars. Sales drops only for used cars with remaining warranty and those sold by franchised dealers. These results imply that consumers do respond to auto makers' financial distress, which could add an additional cost to the existing financial problem faced by auto makers. The third chapter is co-authored with Dr. Andrew Sweeting and Dr. James Roberts and looks at potential entry defense. Horizontal mergers may be approved if antitrust authorities believe that new entry would limit any anticompetitive effects. This `potential entry defense' has led to mergers being approved in concentrated markets in several industries, including airlines. However, entry will be both less likely and less able to constrain market power if the pre-merger entry process already selected the best firms into the market, for example those firms with better product qualities or lower marginal or fixed costs. We estimate a rich empirical entry model allowing for these types of selection using data from airline routes connecting the top 80 airports by enplanement. Our results indicate that selection is important and helps to explain the fact that airline mergers have tended to increase prices without inducing a significant number of new entering firms, even though most of these markets have several potential entrants and, in most cities, entry barriers are relatively low. We also use our model to conduct counterfactual merger analysis. === Dissertation